Farmers’ willingness to take part in Sorghum-based Innovation Platform in Niger State, Nigeria - Mohammed, Ibrahim; Ugochukwu Adonikam, Nnanna (Journal of Extension Education, 2020)
The research examined the determinants of farmers’ willingness to partake in sorghumbased innovation platforms, ascertained the factors influencing their willingness and constraints to their participation. Structured questionnaire was used to elicit data from 350 registered respondents drawn from Niger State, Nigeria. Data were analysed using descriptive statistics, Probit and multiple regression. The result reveals that the farmers’ mean age was 40. About 85 % of them were married with a household size of 1-5 persons. The result of probit showed that availability of active labour force, income from the sorghum, number of trainings, access to extension service and market access were the major determinants to farmers’ participation in sorghum innovation platform. Major constraints were, untimely meetings, poor means of transportation, information gap and complexity of innovation. The study concludes that farmers were willing to participate in sorghum-based innovation platform but do not have enough capital base. The study recommends that farmers should be linked up with credit institutions and timely meetings should be conducted